Harvest Method, Cultivar, and Time of Swathing Effects on Yield and Oil Content of Winter Canola - M. J. Stamm; S. J. Dooley; K. L. Roozeboom (Kansas Agricultural Experiment Station Research Reports, 2019)
Producers want to achieve the highest yield and oil content possible using either swathing or direct cutting to harvest winter canola. Multi-year experiments were conducted to evaluate the effects of harvest method (swathing versus direct cutting) and cultivar on seed moisture, yield, and oil content; and to evaluate the effects of swathing timing on yield and oil content. The harvest method experiments were conducted for two seasons at the Redd Foundation Field near Partridge, KS. The time of swathing experiments were conducted for two seasons near Manhattan, KS. In 2016 and 2017, harvest method had a significant effect on seed moisture, yield, and oil content. Swathing produced seed with lower moisture content and greater yield, but direct cutting produced seed with the highest oil content. Cultivars differed in their response to yield depending on the harvest method used. Some cultivars responded positively to swathing, others responded positively to direct cutting, and some showed no response to harvest method. Time of swathing had a significant effect on yield and oil content. As a rule, as seed color change progressed, yield and oil content increased. All swathing treatments had greater yield than direct cutting except when swathing was done at green seed. Seed from direct cutting had significantly greater oil content than seed from all swathing treatments. Both swathing and direct cutting can be used effectively to harvest winter canola.
Keywords: canola; harvest; oil content; swathing; direct cutting; seed color change